Principles Of Justice And Civil Society: Theoretical Foundations - Sadullayeva Shahnoza Bahodirovna (Genius Publishing Group, 2025)
This article theoretically explores the essence of the principles of justice, their role within civil society, and the interconnection between the two. Justice, as a fundamental value of civil society, is closely linked to human rights, equality, rule of law, and social responsibility. The article analyzes the historical development of the concept of justice, modern approaches to it, and its significance in building a democratic society. Furthermore, it discusses the institutional mechanisms of civil society including nongovernmental organizations, mass media, educational institutions, and public councils as key structures through which justice can be realized in practice
Keywords: principles of justice; civil society; legal consciousness